2002
DOI: 10.1002/cncr.10829
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rel/NF‐κB transcription factors in apoptosis of human hepatocellular carcinoma cells

Abstract: BACKGROUNDPrimary hepatocellular carcinoma (HCC) is one of the 10 most common human carcinomas in the world. The mechanism by which HCC cells resist apoptosis induced by various treatment modalities is poorly understood.METHODSThe authors sought to determine whether Rel/NF‐κB transcription factors play a key role in controlling apoptosis in human HCCcells. We assessed constitutive and inducible activation of NF‐κB in hepatitis B virus (HBV)‐positive (Hep3B) and in hepatitis virus‐negative (Chang, HepG2) HCC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 44 publications
2
55
0
Order By: Relevance
“…Others have also found that HCC cells constitutively express high levels of NF-κB. 5,46,47 In the present study, ARL-6 cells were more responsive to H 2 O 2 -mediated activation of NF-κB than normal hepatocytes, as shown by translocation of the p65 subunit of NF-κB to the nucleus, and enhanced DNA binding by EMSA assay. In other work (Qiao et al, unpublished data) we have found similar results for the human HCC cell line, HuH7.…”
Section: Discussionsupporting
confidence: 62%
“…Others have also found that HCC cells constitutively express high levels of NF-κB. 5,46,47 In the present study, ARL-6 cells were more responsive to H 2 O 2 -mediated activation of NF-κB than normal hepatocytes, as shown by translocation of the p65 subunit of NF-κB to the nucleus, and enhanced DNA binding by EMSA assay. In other work (Qiao et al, unpublished data) we have found similar results for the human HCC cell line, HuH7.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, the Ras/MAP kinase pathway, which has been shown to block cell death in other systems, was not involved in RTKN-mediated antiapoptosis. Elevated NF-kB activity has been found in a number of malignant tumors (Arlt et al, 2002;Bhat-Nakshatri et al, 2002;Chiao et al, 2002). Permanent amplification of NF-kB activity may involve mutations and/or over-representation of members of the Rel protein family (Romero and Humphries, 1995), IkBa gene, or IKKs (DiDonato et al, 1997;RomieuMourez et al, 2001;Sanlioglu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NF-B plays an important role in liver carcinogenesis (64,65). Activation of NF-B was observed frequently in hepatocarcinoma, and the essential role of NF-B for cancer growth was confirmed in several human cancer cell lines (66,67). Therefore, control of NF-B activity may be an important therapeutic target for the treatment of human hepatocarcinoma (68).…”
Section: Fig 3 Activation Of Nf-b During Er Stressmentioning
confidence: 99%